2016
DOI: 10.1039/c5ee03229f
|View full text |Cite
|
Sign up to set email alerts
|

Intermixing-seeded growth for high-performance planar heterojunction perovskite solar cells assisted by precursor-capped nanoparticles

Abstract: A novel approach to modulate the nucleation and growth of perovskite crystals by intermixing precursor-capped nanoparticles has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 37 publications
4
129
1
Order By: Relevance
“…As a result, crystallites of significant smaller size are obtained. In case of PbHPO 3 NPs containing precursors, we propose a mechanism similar to the one from Li et al who reported the functionality of PbS nanocrystals for a nucleation‐assisted growth of perovskite domains in thin films. As a result, obtained crystallite domains were larger if compared with c‐MAI‐based precursor as well as enhanced crystallinity supported by XRD (Figure i) and photophysical study ( Figure a,b).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As a result, crystallites of significant smaller size are obtained. In case of PbHPO 3 NPs containing precursors, we propose a mechanism similar to the one from Li et al who reported the functionality of PbS nanocrystals for a nucleation‐assisted growth of perovskite domains in thin films. As a result, obtained crystallite domains were larger if compared with c‐MAI‐based precursor as well as enhanced crystallinity supported by XRD (Figure i) and photophysical study ( Figure a,b).…”
Section: Resultssupporting
confidence: 65%
“…Such devices demonstrate higher efficiency compared to the ones produced from stoichiometric precursor, because films with larger perovskite domains display better crystal quality due to reduced area of grain boundaries (GB) and therefore less defects. Li et al have also demonstrated that direct incorporation of the PbS nanoparticles (NPs) with the size of 5 nm creates nucleation sites for larger perovskite crystal domain. These data inspired us for a deeper study of the perovskite precursor system to ultimately understand the nature of the impurities and their impact on perovskite film formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the surface passivation ligands with low lattice mismatch, high‐quality, large‐scale grain and nonporous perovskite films incorporated with QDs could benefit hybrid photodetectors. Li et al and Thi Tuyen et al independently reported that the nucleation and growth of perovskite crystal grain size can be effectively tuned by the embedded PbS QDs. Li et al demonstrated the QDs play a crucial role in the nucleation of perovskite crystals via an intermixing‐seeded growth technique.…”
Section: Hybrid Structure Of Halide‐perovskite‐based Photodetectorsmentioning
confidence: 99%
“…Li et al and Thi Tuyen et al independently reported that the nucleation and growth of perovskite crystal grain size can be effectively tuned by the embedded PbS QDs. Li et al demonstrated the QDs play a crucial role in the nucleation of perovskite crystals via an intermixing‐seeded growth technique. Thi Tuyen et al found that the grain size of perovskite films with QDs was 4.5‐fold larger than that of pristine perovskite films.…”
Section: Hybrid Structure Of Halide‐perovskite‐based Photodetectorsmentioning
confidence: 99%
“…With the aid of ultraviolet-ozone treatment for FTO, the perovskite film exhibited large grains, a low density of pin holes, as well as a smooth surface. Li and co-workers [33] demonstrated a novel intermixing-seeded growth technique to obtain high-performance planar heterojunction PSCs (Figs 3c-f). Through interfacial engineering with ligand-exchange treatment, a small amount of methylammonium iodide (MAI)-capped PbS nanoparticles intermixed with the perovskite precursor solution, serving as nucleation sites to promote the formation of the inorganic framework of perovskite lattice structures.…”
Section: Conventional Structured Pscsmentioning
confidence: 99%